Back to industry: Evaluating women's return to chartered accreditation post-maternity in the built environment sector professions - Sinead Clarkson; Lucy Hind (Administrative Sciences, 2024)
Efforts have been made to improve gender diversity in the built environment professions. This sector continues to experience growth restrictions due to skill shortages. Some progress has been made at the entry level; however, the retention of women in professional roles within this sector continues to present a challenge. Support for women during maternity, upon return to work and while working with family has been identified as a barrier to women's progression in this sector. Professional bodies are uniquely placed to support their female members. Therefore, this study had two aims: to examine current professional body support for members during and after maternity leave and to examine the experiences of female professionals, who have taken maternity leave whilst holding membership in a built environment professional body. This study adopted an embedded, mixed-method design, using a secondary, qualitative data set to augment the primary, quantitative data set, within one phase. Surveys were distributed directly to professional bodies and to professionals via social media (LinkedIn). The survey of the professional bodies identified a varied approach to maternity support. The professional member survey identified a lack of awareness of available support, and generally the need for more support during maternity and on return to work. In summary, professional bodies in the built environment could improve maternity support for members by improving communication and achieving parity in support across the various disciplines.
Keywords: 350; construction skills; employment; gender equality; maternity; skills shortage; women in construction